Cationic, amphiphilic copolymer micelles as nucleic acid carriers for enhanced transfection in rat spinal cord. (15th April 2016) - Gwak, So-Jung; Nice, Justin; Zhang, Jeremy; Green, Benjamin; Macks, Christian; Bae, Sooneon; Webb, Ken; Lee, Jeoung Soo
Graphical abstract: Abstract: Spinal cord injury commonly leads to permanent motor and sensory deficits due to the limited regenerative capacity of the adult central nervous system (CNS). Nucleic acid-based therapy is a promising strategy to deliver bioactive molecules capable of promoting axonal regeneration. Branched polyethylenimine (bPEI: 25 kDa) is one of the most widely studied nonviral vectors, but its clinical application has been limited due to its cytotoxicity and low transfection efficiency in the presence of serum proteins. In this study, we synthesized cationic amphiphilic copolymers, poly (lactide-co-glycolide)-graft-polyethylenimine (PgP), by grafting low molecular weight PLGA (4 kDa) to bPEI (25 kDa) at approximately a 3:1 ratio as an efficient nonviral vector. We show that PgP micelle is capable of efficiently transfecting plasmid DNA (pDNA) and siRNA in the presence of 10% serum in neuroglioma (C6) cells, neuroblastoma (B35) cells, and primary E8 chick forebrain neurons (CFN) with pDNA transfection efficiencies of 58.8%, 75.1%, and 8.1%, respectively. We also show that PgP provides high-level transgene expression in the rat spinal cord in vivo that is substantially greater than that attained with bPEI. The combination of improved transfection and reduced cytotoxicity in vitro in the presence of serum and in vivo transfection of neural cells relative to conventional bPEI suggests that PgP may be a promising nonviral vector for therapeutic nucleic acid delivery for neural regeneration. Statement of Significance: Gene therapy is a promising strategy to overcome barriers to axonal regeneration in the injured central nervous system. Branched polyethylenimine (bPEI: 25 kDa) is one of the most widely studied nonviral vectors, but its clinical application has been limited due to cytotoxicity and low transfection efficiency in the presence of serum proteins. Here, we report cationic amphiphilic copolymers, poly (lactide-co-glycolide)-graft-polyethylenimine (PgP) that are capable of efficiently transfecting reporter genes and siRNA both in the presence of 10% serum in vitro and in the rat spinal cord in vivo . The combination of improved transfection and reduced cytotoxicity in the presence of serum as well as transfection of neural cells in vivo suggests PgP may be a promising nucleic acid carrier for CNS gene delivery.